THE POLITICS OF HALAL LABEL: BETWEEN ECONOMIC PIETY AND RELIGIOUS AMBIGUITY - Mokhamad Zainal Anwar; Yuyun Sunesti; Ihsan Ihsan (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
The use of the halal label was expanded. Label, which is originally shown on food and beverage products only, but currently also shown on non-food and beverage products, such as tissue, pan, and refrigerator. It is a phenomenon of halalization; an expansion of halal labels for the product consumed by the Muslim community. Based on the qualitative method, the results of this study show that the Millennial Muslim generation's understanding of halal is varying and affected by varying sources of knowledge and internet use. Knowledge source no longer lies onÂ Kiai/UstadzÂ only, but also on search engines available in cyberspace. Social media and the internet also become media used by the millennial Muslim generation to search for information on the product' rightfulness. The millennial Muslim generation just wants to use a product with a halal label, and an affordable price. If it is unaffordable, they will choose other affordable products volitionally despite no halal label. The contestation in selecting and non-selecting the halal label shows the existence of interests and authority for the millennial Muslim generation. This is what is called the politics of the halal label.